Evaluation of seedling age and nutrient sources on phenology, yield and agrometeorological indices for sweet corn (Zea mays saccharata L.) - Jan, Bisma; Bhat, M. Anwar; Bhat, Tauseef A.; Yaqoob, Munazah; Nazir, Aijaz; Bhat, M. Ashraf; Mira, Amir H.; Wani, Fehim J.; Singh, Jitendra Kumar; Kumar, Rajesh; Gasparovic, Kristina; He, Xiaolan; et al. (Elsevier, 2021)
The field experiment was conducted during Kharif season of 2020 at Agronomy farm of Faculty of Agriculture, Wadura, SKUAST-K to study the influence of age of seedling and sources of nutrients on phenology, yield and agrometeorological indices for sweet corn. The experiment included two factors viz. age of seedlings (12, 22 and 32 days old seedling) and sources of nutrients (control, RDF, 50 percent RDF + FYM @ 12 t ha−1, 50 percent RDF + vermi-compost @ 4 t ha−1 and 50 percent RDF + poultry manure @ 2 t ha−1) tested in RCBD with three replications. Transplanting 12 days old seedlings required maximum number of days to attain different phenological stages, thereby accumulated maximum heat units followed by 22 days old seedlings. While as transplanting 22 days old seedling recorded significantly highest HUE, HTUE, PTUE and HyTUE and consequently resulted in the highest green cob and biological yield compared to other ages of seedlings. Among various sources of nutrients, application of 50 per cent RDF + poultry manure @ 2 t ha−1 took maximum number of days to attain various phenophases thereby accumulated maximum heat units and registered highest HUE, HTUE, PTUE and HyTUE followed by application of 100 per cent RDF.